1976
DOI: 10.1073/pnas.73.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of growth delay induced in Escherichia coli by near ultraviolet radiation.

Abstract: Continuously growing cultures of E. coli B/r were irradiated with a fluence of broad-band near-ultraviolet radiation (315-405 nm) sufficient to cause extensive growth delay and complete cessation of net RNA synthesis. Chloramphenicol treatment was found to stimulate resumption of RNA synthesis, similar to that observed with chloramphenicol treatment after amino-acid starvation. E. coli strains in which amino-acid starvation does not result in cessation of RNA synthesis ("relaxed" or ret strains) show no cessat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(60 citation statements)
references
References 22 publications
3
57
0
Order By: Relevance
“…These cross-linked tRNAs are poor substrates for aminoacylation (6,8), leading to the accumulation of uncharged tRNAs (9). This effect mimics amino acid starvation and triggers the stringent response through the synthesis of ppGpp and ApppGpp, which inhibit cell growth and induce the expression of specific proteins that enhance cell survival after the stress (2,4,7,10).…”
mentioning
confidence: 99%
“…These cross-linked tRNAs are poor substrates for aminoacylation (6,8), leading to the accumulation of uncharged tRNAs (9). This effect mimics amino acid starvation and triggers the stringent response through the synthesis of ppGpp and ApppGpp, which inhibit cell growth and induce the expression of specific proteins that enhance cell survival after the stress (2,4,7,10).…”
mentioning
confidence: 99%
“…The s 4 U undergoes a photoactivated 2 Ļ© 2 cycloaddition with cytidine 13 when the tRNA is exposed to light of a wavelength similar to the 334 nm absorbance maximum of s 4 U (13-15). The resulting cross-linked tRNA are poor aminoacylation substrates (16), and the accumulation of uncharged tRNA arrests growth by triggering the stringent response (17,18). Lipsett and co-workers (19,20) investigated the enzymology of s 4 U biosynthesis in Escherichia coli and reported that the overall reaction utilized cysteine as the sulfur donor and required ATP as a substrate.…”
mentioning
confidence: 99%
“…A potential caveat of using UVA irradiation ( , Ļ³335 nm) involves the formation of photo adducts between thiouridine and cytidine at positions 8 and 13 in some tRNAs of E. coli (18), causing an amino acid starvation response. Once the cells are removed from UV exposure, however, the effects are reversed, and they recover by synthesis of new functional tRNAs (19).…”
Section: Photochemistry Of the Unnatural Amino Acids-thementioning
confidence: 99%